Cytomegalovirus-Specific T Cells in Pediatric Liver Transplant Recipients - Songpon Getsuwan; Nopporn Apiwattanakul; Chatmanee Lertudomphonwanit; Suradej Hongeng; Sophida Boonsathorn; Wiparat Manuyakorn; Pornthep Tanpowpong; Usanarat Anurathapan; Kanchana Tangnararatchakit; Suporn Treepongkaruna (Viruses, 2023)
Cytomegalovirus (CMV) infection is a major opportunistic infection after liver transplantation (LT) that necessitates monitoring. Because of the lack of studies in children, we aimed to investigate CMV-specific T cell immune reconstitution among pediatric LT recipients. The recipients were monitored for CMV infection and CMV-specific T cells from the start of immunosuppressive therapy until 48 weeks after LT. Clinically significant CMV viremia (csCMV) requiring preemptive therapy was defined as a CMV load of >2000 IU/mL. Peripheral blood CMV-specific T cells were analyzed by flow cytometry based on IFNγ secretion upon stimulation with CMV antigens including immediate early protein 1 (IE1) Ag, phosphoprotein 65 (pp65) Ag, and whole CMV lysate (wCMV). Of the 41 patients who underwent LT, 20 (48.8%) had csCMV. Most (17/20 patients) were asymptomatic and characterized as experiencing CMV reactivation. The onset of csCMV occurred approximately 7 weeks after LT (interquartile range: 4–12.9); csCMV rarely recurred after preemptive therapy. Lower pp65-specific CD8+ T cell response was associated with the occurrence of csCMV (p = 0.01) and correlated with increased viral load at the time of csCMV diagnosis (ρ = −0.553, p = 0.02). Moreover, those with csCMV had lower percentages of IE1-specific CD4+ and wCMV-reactive CD4+ T cells at 12 weeks after LT (p = 0.03 and p = 0.01, respectively). Despite intense immunosuppressive therapy, CMV-specific T cell immune reconstitution occurred in pediatric patients post-LT, which could confer protection against CMV reactivation.